Examining the Meaning of Riwayah and Dirayah Hadith Science from a Historical Perspective - Achmad Sofyan; Juhairiyah; Faridatul Jannah (Penerbit Hellow Pustaka, 2025)
The science of hadith is not just a science of hearing and writing, but also includes how to research a truth and look for the hidden meaning of the text (Matan), the path of its transmission (Sanad), evidence that supports its truth, guarding against deviations and errors. . Hadith History is a science that examines how the Hadith of Rasulullah SAW is connected or connected in terms of its truth and weakness, the condition of its narrators in Dhabt and how the transmission path is connected or not. Dirayah is studying the rules that tell the situation of the narrators and what they narrate. This opinion is in accordance with the discussion intended in this science, namely knowing the condition of the narrators and their narration, whether they are accepted or rejected. Regarding the writing of Hadith during the time of the Prophet, there are several Hadith spread among the Companions of Radiyallahu 'anhum which state that they were prohibited from writing Nabawi Hadith. At that time, and at the time of their companions, they searched for and reviewed the path of Hadith transmission. Se, what was the condition of the narrators? Are the Peras in it Tsiqqoh (trusted/honest) or vice versa.